ANALYSIS OF PHYSICAL FITNESS AND ATTITUDE OF CONFIDENCE ON PJOK LEARNING OUTCOMES - Novita Yansa; Syafaruddin Syafaruddin; Herri Yusfi (Journal Physical Education, Health and Recreation, 2023)
This study aims to determine the results and relationships of physical fitness and self-confidence towards PJOK learning outcomes in students of SMA Negeri Sumatra Selatan. This type of research is descriptive and uses a correlation design. The population of this study were students of SMA Negeri South Sumatra. The sample of this research is using accidental sampling or accidental sampling which is 30 students. The instruments in this study were for physical fitness tests using the Harvard step test, for self-confidence using a self-confidence questionnaire and for PJOK learning outcomes looking at the results of the report cards of South Sumatra State Senior High School students. Data analysis techniques were processed with percentages and hypothesis testing using correlation tests with the help of a computer in the SPSS 22 excel program. Based on the percentage analysis of the data, the results for physical fitness had an average physical fitness in the good category. The results of self-confidence have an average good category and for PJOK learning outcomes students have very good average results. The normality test results obtained for each variable are normally distributed. The results of the correlation analysis between X1 and Y = 0.85, the values of X2 and Y = 0.85 and the values of X1, X2 and Y = 0.89 show a very strong relationship. The implementation of this study shows that physical fitness and self-confidence have a relationship with PJOK learning outcomes.